2020
DOI: 10.1007/s12308-020-00423-7
|View full text |Cite
|
Sign up to set email alerts
|

Case report: a fatal combination of hemophagocytic lymphohistiocytosis with extensive pulmonary microvascular damage in COVID-19 pneumonia

Abstract: The clinical features of COVID-19 have a considerable range from a mild illness to severe disease. Underlying pathophysiological mechanisms of the rapidly progressive, and often fatal, pulmonary disease frequently observed in COVID-19 need to be elucidated, in order to develop new treatment strategies for different disease endotypes. Fatal cases can display features of a cytokine storm, which may be related to hemophagocytic lymphohistiocytosis. Also, a spectrum of vascular changes, including microvascular dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Child cases (16 years old and younger), and suspected or unproven HLH cases were not included in the study. We found 21 more adult cases diagnosed with COVID-19-associated HLH in addition to ours [9][10][11][12][13][14][15][16][17][18][19]. Eighteen (86%) of the patients were over the age of 50 (range 17-84), 16 (76%) were male, and most of them had at least one underlying disease.…”
Section: Review Of Other Covid-19 Associated Hlh Casesmentioning
confidence: 52%
“…Child cases (16 years old and younger), and suspected or unproven HLH cases were not included in the study. We found 21 more adult cases diagnosed with COVID-19-associated HLH in addition to ours [9][10][11][12][13][14][15][16][17][18][19]. Eighteen (86%) of the patients were over the age of 50 (range 17-84), 16 (76%) were male, and most of them had at least one underlying disease.…”
Section: Review Of Other Covid-19 Associated Hlh Casesmentioning
confidence: 52%
“…There are case reports of SARS-CoV-2-induced sHLH diagnosed antemortem (11)(12)(13)(14)(15) and postmortem (1,(16)(17)(18)(19) while the illness is/was ongoing, as shown in Table 2B. However, the literature is sparse about COVID-19 recovered cases developing sHLH (8)(9)(10), as shown in Table 2B.…”
Section: Discussionmentioning
confidence: 99%
“…Elbadawi et al reported the absolute neutrophil count and not D-dimer, a traditional biomarker associated with thrombosis, is an independent predictor of thrombotic events in patients with COVID-19. 30 The mortality benefit of dexamethasone, an immunosuppressant and anti-inflammatory medication, in hospitalized patients with COVID-19 31 and recent reports of immunothrombosis 17,[32][33][34][35] and microvascular occlusion 18,[36][37][38] by multiple independent groups, suggest platelets may be indirect mediators of thrombosis and perhaps not the best direct targets for pharmacological intervention. Contemporaneous with submission of this manuscript, a smaller, nonpropensity-matched study has shown aspirin treatment decreased mortality that was driven by reduced ICU level care and mechanical ventilatory needs but not thrombosis in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%